Adsorption of Soluble Ammonia Using A Porous Polymer Composite Cu-(TAC) And Activated Carbon Empty Fruit Palm Oil - Zubir, Moondra; Jasmidi; Selly, Rini; Pulungan, Ahmad Shafwan; Miswanda, Dikki; Wardana, Novrizaldi; Rahmah, Siti; Faradilla, Putri; Ramadhan, Dwi Sapri (Universitas Negeri Medan, 2025)
This study aims to determine the stages in the process of making activated carbon, synthesis of porous polymer composites Cu(TAC) and activated carbon composites (KA-Cu(TAC) for adsorption of dissolved ammonia (NH4OH). To know the characterization results of activated carbon and KA- Cu(TAC), as well as knowing the optimum mass, concentration, and contact time of activated carbon KA-Cu(TAC) for the adsorption of dissolved ammonia. The research stages started from Empty Oil Palm Bunches (EFB) used as biosorbents for carbon production at 500oC. The resulting product was activated with H3PO4, then modified with porous polymer Cu(TAC) to make a composite. The KA-Cu(TAC) composite was synthesized by reflux method. Then MOFs, activated carbon and KA-Cu(TAC) composite were characterized by BET. The BET characterization results showed that the successfully synthesized KA-Cu(TAC) composite experienced an increase in surface area.In the NH4OH adsorption process the optimum mass efficiency on activated carbon still increased at 8 grams while the KA-Cu(TAC) composite obtained an efficiency of 36, 6% and optimally at a mass of 4 g. At variations in concentration, the efficiency of the two samples still decreased. And the optimum time efficiency obtained in the NH4OH adsorption process with activated carbon was 70% and the KA-Cu(TAC) composite was 86.6%, both samples were equally optimal at 75 minutes